Development of glass-ceramics from soda lime silica glass waste by direct sintering method for opal imitation - Duangkhae Bootkul (2018)
© 2017 Trans Tech Publications, Switzerland. Natural opal, an amorphous, hydrous form of silica (SiO2-n-H2O), has been one of the favored precious gemstones for many centuries. Though beautiful, opal is very fragile and is damaged quite easily. Thus, opals of all varieties have been synthesized experimentally and commercially. The objective of this project was to synthesize and to compare crystalline opals. In this work, the development of powder sintered glass ceramics process based on soda lime silica glass waste with metal oxide powder enable jewelry applications. The substantial viscous flow of the glass led to dense products for rapid treatments at relatively low temperatures (900-1,000°C), whereas glass/metal powder interactions resulted in the formation of color agent crystals, provide enhancing optical properties. Several techniques were applied for characterization of the ingots. The chemical analysis was performed by Energy Dispersive X-ray Fluorescence (ED-XRF). The mineralogical compositions of the samples were determined by X-ray diffraction analysis. Raman spectroscopy was applied for optical characterization. The results were compared with a natural common opal. The present investigation demonstrated that the common opal with both color and colorless appearance can be synthesized by the technique, as the crystalline phase of opal structure was identified by XRD measurement. There is a great potential for such materials with novel functionalities for artificial gemstone application, i.e. opal forming.